ANTOSHKA AND SVETLYACHOK ARE NEW VARIETIES OF BEAN OF VNIISSOK BREEDING - A. A. Antoshkin; M. P. Miroshnikova; E. P. Pronina (Овощи России, 2015)
As a result of many years breeding, two varieties of southern bean have been developed. Cultivar «Antoshka» is climbing bean for farm gardening. Cultivar «Svetlyachok» is bunch,forming cultivar. Both varieties are suitable for mechanized cultivation. They are characterized by high content of sugars and ascorbic acid. These cultivars are recommended for freezing.